2013
DOI: 10.1080/09540105.2013.864606
|View full text |Cite
|
Sign up to set email alerts
|

Immunological response in mice immunised via oral route with açaí (Euterpe oleraceaMart.)

Abstract: 2015) Immunological response in mice immunised via oral route with açaí (Euterpe oleracea Mart.), Food and Agricultural Immunology, 26:1, 38-45,The açaí berry (Euterpe oleracea Mart.) is a typical fruit of the Amazon region. The consumption of the açaí pulp has grown in both the national and international markets due to its high nutritional and energetic value. The pulp is also rich in phenolic compounds, mainly anthocyanin, giving it antioxidant properties and thereby also the status of being a functional foo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
2
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 22 publications
0
2
1
Order By: Relevance
“…Analyzing IgE and IgG1, positive results were observed in the western blotting test showing that LP used was not able to generate the production of immunoglobulins. This result is relevant because allergic reactions from foods are characterized by specific IgE and IgG1 levels in serum and by activating gut mast cells (Guedes & Pereira, 2005;Oliveira et al, 2013). The western blotting test of the sample used in the present study is not similar to the results reported by Sandeep, Alok, Amita, Anurag, and Bhushan (2011) who evaluated the allergenic responses of BALB/c mice immunized with red kidney beans (P. vulgaris cv.…”
Section: Discussioncontrasting
confidence: 53%
“…Analyzing IgE and IgG1, positive results were observed in the western blotting test showing that LP used was not able to generate the production of immunoglobulins. This result is relevant because allergic reactions from foods are characterized by specific IgE and IgG1 levels in serum and by activating gut mast cells (Guedes & Pereira, 2005;Oliveira et al, 2013). The western blotting test of the sample used in the present study is not similar to the results reported by Sandeep, Alok, Amita, Anurag, and Bhushan (2011) who evaluated the allergenic responses of BALB/c mice immunized with red kidney beans (P. vulgaris cv.…”
Section: Discussioncontrasting
confidence: 53%
“…This food was introduced to the Northeast region and its consumption has increased over the past 10 years. Recent research has suggested its insertion into the group of food allergens [ 26 ]. Among the aforementioned fruits, bananas and avocados are classically related to cross allergy with latex [ 13 ], while there are reports in the literature of contact dermatitis with guava [ 27 ], although with no solid references to food allergy.…”
Section: Discussionmentioning
confidence: 99%
“…According to Pereira and Guedes (2005) and Oliveira et al (2013), the allergic reactions from foods are characterized by specific IgE and IgG1 levels in serum and by activating gut mast cells.…”
Section: Discussionmentioning
confidence: 99%